Information Retrieval System for Online Food Ordering Using the Vector Space Model Method - Saifulloh Rifai (Institute of Computer Science (IOCS), 2021)
The development of start-up in Indonesia continues to grow along with increasingly sophisticated technology developments, this is one of the business opportunities from sharing start-up in Indonesia, and everyone is always given the convenience of every activity that is being experienced by millennial. Speed ??and accuracy in the information search process have become mandatory. In order to facilitate the search process or find the required information, the aim of this study is to provide a general description of the restaurant search process from online food ordering applications. The implementation of the theory applied in this study uses the vector space model method, with the token and indexing process so that results are found according to the keywords inputted in the application, and will be compared with the data contained in the application, so that it can produce the correct information.